2005
DOI: 10.1007/s00424-005-1425-3
|View full text |Cite
|
Sign up to set email alerts
|

Cut-off phenomenon in the protective effect of alcohols against lysophosphatidylcholine-induced calcium overload

Abstract: We studied the effect of chain length on the protective effect of alcohols against lysophosphatidylcholine (LPC)-induced Ca2+ overload in neonatal rat cardiomyocytes. We previously found that ethanol retards Ca2+ elevation. Cells were loaded with the Ca2+-sensitive fluorophore fura-2, and changes in fluorescence were followed. The addition of 10 microM LPC increased Ca2+, which reached a plateau after an 8-10 min delay. The presence of 88 mM n-propanol, n-butanol, tert-butanol, or 2,2-dimethylpropanol signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Bordeleau et al (Bordeleau et al, 2005) studied the ability of different alcohols to prevent lysophosphatidylcholine (LPC)-induced Ca 2+ overload in rat cardiomyocytes, loaded with a calcium sensitive fluorophore. They tested the straight chain alcohols ethanol, n-propanol, n-butanol, and n-pentanol as well as some branched chain alcohols at 88 mM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bordeleau et al (Bordeleau et al, 2005) studied the ability of different alcohols to prevent lysophosphatidylcholine (LPC)-induced Ca 2+ overload in rat cardiomyocytes, loaded with a calcium sensitive fluorophore. They tested the straight chain alcohols ethanol, n-propanol, n-butanol, and n-pentanol as well as some branched chain alcohols at 88 mM.…”
Section: Discussionmentioning
confidence: 99%
“…Biological effects of other lower straight and branched chain alcohols had been tested on cell cultures (Bordeleau et al, 2005) and laboratory animals (Feller and Crabbe, 1991). In a study by Song et al, the effects of methanol, ethanol, 1-propanol, and n-butanol on TNF-α secretion were tested in an epithelial cell line by ELISA and other methods.…”
Section: Introductionmentioning
confidence: 99%
“…When we studied the effect of different alcohols, we found that the increase in critical micellar concentration of LPC by n-alcohols was proportional to chain length (83). However, as the alcohol chain length increased, the protection against LPC-induced Ca 2+ overload decreased and disappeared completely with n-pentanol, implying that micelle formation was not involved in the extension of the lag time.…”
Section: Arrhythmias During Myocardial Ischemiamentioning
confidence: 97%